Transient Flashes in Saturn’s UV Aurora: An Analysis of Hubble Space Telescope 2013–2017 Campaigns and Cassini Magnetic Field Measurements - Tianshu Qin; Sarah V. Badman; Joe Kinrade; Alexander Bader (Universe, 2022)
We examined Hubble Space Telescope images of Saturn’s northern UV aurora in 2013–2017, identified 29 short-lived flashes, and examined simultaneous magnetometer data collected by the Cassini orbiter. When observation cadence permitted, a flash lifetime of 4–17 min (subject to exposure time-related uncertainties), and a 40–70 min recurrence period were found. An occurrence map shows a strong preference in both local time (14–19 LT) and latitude (75–85<semantics>°</semantics>). These transient flashes are identified in both the presence and absence of Saturn’s main auroral oval, indicating the lack of dependence on the main emission power. The concurrent magnetic field pulsations generally form a sawtooth shape, and the local field strength experiences a change of 0.2 to 2.0 nT (depending on the distance of Cassini). The quasiperiodic pulsation events were all detected when the spacecraft was in the southern hemisphere with conjugate flashes in northern aurora, suggesting these events occur on closed field lines, and typically showing a sudden transition to a less lagging, more southward magnetic field configuration. We also found the ionospheric footprint of the spacecraft must be close to the region of flashes for magnetic field pulsations to be detected, implying a localised rather than global driving process.